De l’effet de sidération et de peur dans les autoportraits d’Andy Warhol - Marie CORDIÉ-LEVY (E-REA)
The following article analyses the way fear and shock appear in Andy Warhol’s last self portraits, produced in 1986, through the mechanisms that oppose and accompany it. Using the technique of the tactile micro-analysis inspired by historian Carlo Ginzburg and art historian Aloïs Riegl, we will attempt to decipher the effects of fear and shock by referring to the different stages defined by Roger Caillois as composing fear: travestissement, camouflage, and bullying. This representation of fear through the medium of photography and serigraphy simultaneously conforms to the tradition of the pictorial expressions of fear such as can be seen in Caravaggio, while also renewing the concept by introducing traits more typical of the American psyche: a close up view of the character and a touch of the surreal, which could be considered as the modern form of eternity.